MODULE OF LEADERSHIP EXCELLENCE PROGRAMME FOR CHIEF LIBRARIANS & DEPUTY CHIEF LIBRARIANS OF HIGHER EDUCATION INSTITUTION - Zaharah Abd Samad; Aryanti Ahmad; Salawati Ahmad (ExceLib 2022, 2023)
The ExceLib programme is the Ministry's initiative to strengthen the generic leadership and leadership function of senior academic library officers through the presentation of topics and content of leadership modules based on identified current competencies. A total of 31 sessions comprising the seven leadership modules were conducted by speakers from their respective field.